Achievable ADC Performance by Postcorrection Utilizing Dynamic Modeling of the Integral Nonlinearity. (30th March 2008) - Björsell Björsell, Niclas Niclas; Händel Händel, Peter Peter
Abstract : There is a need for a universal dynamic model of analog-to-digital converters (ADC's) aimed for postcorrection. However, it is complicated to fully describe the properties of an ADC by a single model. An alternative is to split up the ADC model in different components, where each component has unique properties. In this paper, a model based on three components is used, and a performance analysis for each component is presented. Each component can be postcorrected individually and by the method that best suits the application. The purpose of postcorrection of an ADC is to improve the performance. Hence, for each component, expressions for the potential improvement have been developed. The measures of performance are total harmonic distortion (THD) and signal to noise and distortion (SINAD), and to some extent spurious-free dynamic range (SFDR).